2017
DOI: 10.1080/10715762.2017.1416112
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase 4 mediates ROS production in radiation-induced senescent cells and promotes migration of inflammatory cells

Abstract: Excessive DNA damage induced by ionising radiation (IR) to normal tissue cells is known to trigger cellular senescence, a process termed stress-induced premature senescence (SIPS). SIPS is often accompanied by the production of reactive oxygen species (ROS), and this is reported to be important for the initiation and maintenance of SIPS. However, the source of ROS during SIPS after IR and their significance in radiation-induced normal tissue damage remain elusive. In the present study, we tested the hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 61 publications
0
31
0
Order By: Relevance
“…ROS can be derived from different sources, including the mitochondria electron transport chain, xanthine oxidase, the cytochrome P450 system, uncoupled nitric oxide synthase, and myeloperoxidase. ROS also mainly comes from two main parts, mitochondrial and NADPH oxidase after radiation ( Bedard and Krause, 2007 ; Bhattacharyya et al., 2014 ; Cho et al., 2017 ; Pei et al., 2017 ; Kawamura et al., 2018 ; Sakai et al., 2018 ; Shimura et al., 2018 ; Mortezaee et al., 2019 ). To explore the origin of ROS induced by 1α,25(OH) 2 D 3 , both NADPH oxidase inhibitors, DPI and Apocynin, and the mitochondrial membrane potential were used to determine the source of ROS ( Bedard and Krause, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…ROS can be derived from different sources, including the mitochondria electron transport chain, xanthine oxidase, the cytochrome P450 system, uncoupled nitric oxide synthase, and myeloperoxidase. ROS also mainly comes from two main parts, mitochondrial and NADPH oxidase after radiation ( Bedard and Krause, 2007 ; Bhattacharyya et al., 2014 ; Cho et al., 2017 ; Pei et al., 2017 ; Kawamura et al., 2018 ; Sakai et al., 2018 ; Shimura et al., 2018 ; Mortezaee et al., 2019 ). To explore the origin of ROS induced by 1α,25(OH) 2 D 3 , both NADPH oxidase inhibitors, DPI and Apocynin, and the mitochondrial membrane potential were used to determine the source of ROS ( Bedard and Krause, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, upregulation of Nox4 by ionizing radiation induces SIPS in MEFs. Nox4-derived ROS production was associated with increased migration of monocytes, supporting a role of ROS in the recruitment of inflammatory cells into irradiated tissues [ 106 ]. In endothelial cells, upregulation of Nox4 during aging causes endothelial dysfunction mediated by endoplasmic reticulum (ER) stress, leading to eNOS uncoupling [ 107 ].…”
Section: Nox4 In Senescencementioning
confidence: 99%
“…Therefore, it seems that the major inhibition pathway of anti‐inflammation by R or NIR irradiation is through Nox4‐MyD88‐NF‐κB in this model (see Figure S4, Supporting Information). It has been reported that ionizing radiation or blue light (405 nm) irradiation exhibited enhancement of Nox4 expression level and ROS production, while those induced ROS productions could be diminished by inhibiting Nox4 expression level genetically or pharmacologically 51,52. Our data showed that the production of ROS can be regulated by R or NIR irradiation without using any drugs, indicating a potent of PBM therapy as a Nox4 regulator.…”
Section: Discussionmentioning
confidence: 50%